Role of Two Efflux Proteins, ABCB1 and ABCG2 in Blood-Brain Barrier Transport of Bromocriptine in a Murine Model of MPTP-Induced Dopaminergic Degeneration - Sarah Vautier; Aline Milane; Christine Fernandez; Helene Chacun; Lucette Lacomblez; Robert Farinotti (Frontiers Media S.A., 2009)
Purpose: MPTP-induced dopaminergic degeneration is an experimental model commonly used to explore Parkinson's disease. Cerebral drug transport by ABC transporters in MPTP models has never been reported. Methods: We have investigated the transport of bromocriptine through the blood-brain barrier (BBB) in a MPTP model to understand the influence of the dopaminergic degeneration on ABCB1 and ABCG2. Results: We have shown that in MPTP treated mice, bromocriptine is widely distributed to brain (2.3-fold versus control, p